2022
DOI: 10.3390/plants11050631
|View full text |Cite
|
Sign up to set email alerts
|

Diversity Assessment and DNA-Based Fingerprinting of Sicilian Hazelnut (Corylus avellana L.) Germplasm

Abstract: The characterization of plant genetic resources is a precondition for genetic improvement and germplasm management. The increasing use of molecular markers for DNA-based genotype signature is crucial for variety identification and traceability in the food supply chain. We collected 75 Sicilian hazelnut accessions from private and public field collections, including widely grown varieties from the Nebrodi Mountains in north east Sicily (Italy). The germplasm was fingerprinted through nine standardized microsate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 76 publications
0
3
0
3
Order By: Relevance
“…Within the scope of the study, 15 standard varieties and 46 genotypes were clustered in the group numbered 2.2.2. Fiore et al (2022), in their study conducted with 9 SSR primers in 75 hazelnut genotypes selected from the Sicily region.Authors reported that they distinguished between local genotypes and commercial varieties and that the Nebrodi genotypes examined showed significant differences from Northern Italian, Iberian, and Turkish genotypes.…”
Section: Resultsmentioning
confidence: 99%
“…Within the scope of the study, 15 standard varieties and 46 genotypes were clustered in the group numbered 2.2.2. Fiore et al (2022), in their study conducted with 9 SSR primers in 75 hazelnut genotypes selected from the Sicily region.Authors reported that they distinguished between local genotypes and commercial varieties and that the Nebrodi genotypes examined showed significant differences from Northern Italian, Iberian, and Turkish genotypes.…”
Section: Resultsmentioning
confidence: 99%
“…Similarity value was essential for clustering analysis for dendrogram construction (Wangiyana et al 2022). This systematic step has been used recently for genetic diversity studies based on microsatellite DNA fingerprinting (Driskill et al 2022;Fiore et al 2022). This research also applied microsatellite DNA fingerprinting to study horse population genetic diversity.…”
Section: Resultsmentioning
confidence: 99%
“…Уровни средней ожидаемой гетерозиготности (Ho) и средней наблюдаемой гетерозиготности составили 0,54 и 0,26, соответственно, что было ниже, чем в других исследованиях фундука. Например, при изучении 30 образцов фундука из различных районов Италии с 9 локусами SSR средние значения He и Ho составили 0,67 и 0,82, соответственно [15]. Также в аналогичном исследовании, при изучении генетического разнообразия 20 образцов C. avellana уровни He и Ho составили 0,68 и 0,70, соответственно [17].…”
Section: таблица 1 характеристика Ssr-праймеровunclassified
“…В большинстве случаев оценка коллекций, идентификация генотипов, сортов, линий и гибридов основывается на морфологических признаках [27,30], однако число этих признаков ограничено, непостоянно, может зависеть от факторов среды и не всегда позволяет различить близкородственные образцы или сорта. Современные методы на основе молекулярных ДНК-маркеров являются наиболее эффективным инструментом для грамотного пользования геноресурсами, совершенствования сортимента и изучения генетического разнообразия, а также пополнения коллекции донорами новых признаков и дистантными генотипами [15,31].…”
unclassified
See 1 more Smart Citation